Magnetic images of the disintegration process of tablets in the human stomach by ac biosusceptometry - Cora, A.; Andreis, U.; Romeiro, Fernando Gomes [UNESP]; Americo, M. F.; Oliveira, R. B.; Baffa, O.; Miranda, JRA (Iop Publishing Ltd, 2005)
Oral administration of solid dosage forms is usually preferred in drug therapy. Conventional imaging methods are essential tools to investigate the in vivo performance of these formulations. The non-invasive technique of ac biosusceptometry has been introduced as an alternative in studies focusing on gastrointestinal motility and, more recently, to evaluate the behaviour of magnetic tablets in vivo. The aim of this work was to employ a multisensor ac biosusceptometer system to obtain magnetic images of disintegration of tablets in vitro and in the human stomach. The results showed that the transition between the magnetic marker and the magnetic tracer characterized the onset of disintegration (t(50)) and occurred in a short time interval (1.1 +/- 0.4 min). The multisensor ac biosusceptometer was reliable to monitor and analyse the in vivo performance of magnetic tablets showing accuracy to quantify disintegration through the magnetic images and to characterize the profile of this process.